A Comparative Study of Blasphemy Law in Indonesia and America: Religious and Legal Aspects - Puspaningrum, Febrianti Dwi; Adhi, Christoper Theovino; Satrio, Adrianus Sandy Darmawan (Faculty of Law, Universitas Negeri Semarang, 2023)
Blasphemy laws serve as contentious intersections of religious belief and legal governance, reflecting the complex relationship between state authority and individual freedoms. This comparative study explores the dynamics of blasphemy laws in two diverse contexts: Indonesia and the United States. Indonesia, as the world's most populous Muslim-majority nation, exemplifies a predominantly Islamic legal framework, while the United States, renowned for its constitutional protections of free speech, offers a contrasting perspective rooted in secular principles. Drawing upon religious, cultural, and legal dimensions, this research scrutinizes the origins, evolution, and enforcement of blasphemy laws in both countries. It examines the socio-political contexts that shape interpretations of blasphemy, exploring the role of religion in public discourse and legal jurisprudence. Furthermore, it delves into case studies and landmark legal rulings to discern the practical implications of blasphemy laws on religious minorities, freedom of expression, and societal cohesion. By juxtaposing these two distinct legal landscapes, this study aims to illuminate the complexities inherent in navigating religious sensitivities within legal frameworks, as well as the broader implications for human rights and democratic governance. Through an interdisciplinary approach, it seeks to foster a nuanced understanding of the multifaceted interactions between religion, law, and society, thereby contributing to scholarly discourse and policy dialogue on issues of religious freedom and legal pluralism in an increasingly interconnected world.